Truthmaking for Modal Skeptics1. (2nd January 2014) - Asay, Jamin
Abstract Standard truthmaker theory has generally assumed a realist account of de re modality and essences. But there are reasons to be skeptical about such a view, and for considering antirealist alternatives. Can truthmaker theory survive in the face of such skepticism? I argue that it can, but that only certain antirealist perspectives on de re modality are acceptable for truthmaker theory. In particular, either a quasi‐realist or conventionalist account of de re modality is needed to provide the best account of essential and accidental features that can be put to work in truthmaker theory. An important consequence of this approach is that it offers an account of truthmaking that is consistent with a nominalist perspective on properties, and yet fully respects the ontological ambitions driving truthmaker theory.